(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Concrete is a highly consumed material in construction field due to its advantages because of this the natural resources are depleting day by day at an alarming rate and there is an immediate need for finding alternate materials to the natural materials in concrete. So, in my study M30 grade concrete is adopted and the cement was replaced with Egg Shell powder with different percentages of 5%, 10%, 15% and 20% and M-Sand with a constant percentage of 40%. Concrete was casted, cured and then Compressive, Split Tensile and Flexural tests were carried out to find the best combination which results in optimum percentage of strength. The optimum percentage egg shell powder (ESP) is obtained at15%. At optimum ESP the Fine Aggregate is replaced with M-Sand with a constant percentage of 40%. It is the best solution for disposing of used egg shell and to solve the scarcity of sand.